Discovering Bridget Manningham's Rivall friendship
1 online resource
Keywords: This collection of essays represents the very first effort to assess the importance of Bridget Manningham's Rivall Friendship, a seventeenth-century manuscript that concerns the English Civil War, surviving in only one copy at the Newberry Library, Chicago, IL. Bridget Manningham is introduced as the granddaughter of the sixteenth-century diarist John Manningham and as the older sister of Thomas Manningham who was Bishop of Chichester in the early eighteenth century. These essays offer definitive analyses of such early modern issues as the intersection of gender and class, linguistic features of early modern syntax, rhetorical defenses of the royalist position, theories of early modern friendship, plot construction and narrative strategies, and the transition from the romance to the novel.